Application Of Hira And Spar-H Method To Control Work Accident - Cindy Beauty Sijabat; Sunday Noya (Department Industrial Engineering, University of Muhammadiyah Malang, 2014)
The accident occurred in industry is one of the causes of work disruption or cessation. Work accident should be avoided because of causing risk for company. PT “X” is a tobacco company which has a high level of work accident. Therefore, it is necessary to establish a particular effort in order to prevent and reduce the accident. Hazard Identification and Risk Analysis (HIRA) is the method aims to identify any risk types included in the work operation. Where as Standardized Plant Analysis Risk Human Reliability Assessment (SPAR-H) is the method aims to find out the possibility of human error occurrence in the work operations. Based on the research conducted, it can be concluded that the accident occurred in PT. “X” is caused by environmental condition and insecure workers’ action, and inappropriateness with HSE procedures. PT “X” should enroll some corrective actions so the accident can be reduced. In this study, PT “X” should create improvement through administrative action and the use of safety equipment.